Gamificación como estrategia didáctica para estudiantes con dislexia de EGB superior, en la Escuela de Educación Básica “Fe y Alegría” de la Ciudad de Riobamba. - Quisnancela Quisnancela, Ana María (2022)
The present research work is called Gamification as a didactic strategy for students with dyslexia of EGB superior, in the School of Basic Education "Fe y Alegría" of the City of Riobamba; which arises in response to the problem where students present a delay in the aptitude of reading and writing, presenting a clear delay in school development, where slowness in reading, distorted spelling, lack of rhythm and punctuation in sentences, causing also a poor reading comprehension is observed; In this context, the general objective is to propose gamification as a didactic strategy for students with dyslexia in the "Fe y Alegría" Basic Education School in the city of Riobamba. In order to achieve this objective, a research with a qualitative and quantitative approach is designed, through a non-experimental design, with a typology, whose research methods to be used are descriptive, bibliographic; finally, it is concluded that children with dyslexia of upper EGB of the School of Basic Education "Fe y Alegria", present greater difficulty in the auditory and visual recognition of syllables; memorization and recognition of word pairs; reordering of letter/s in words; recognition and segmentation of words in the sentence; auditory and visual recognition of complex words, aspects considered in the final proposal.